2013
DOI: 10.1159/000354321
|View full text |Cite
|
Sign up to set email alerts
|

Occurence of Internet Addiction in a General Population Sample: A Latent Class Analysis

Abstract: Background: Prevalence studies of Internet addiction in the general population are rare. In addition, a lack of approved criteria hampers estimation of its occurrence. Aims: This study conducted a latent class analysis (LCA) in a large general population sample to estimate prevalence. Methods: A telephone survey was conducted based on a random digit dialling procedure including landline telephone (n = 14,022) and cell phone numbers (n = 1,001) in participants aged 14-64. The Compulsive Internet Use Scale (CIUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
124
6
24

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 24 publications
17
124
6
24
Order By: Relevance
“…In a German sample with age 14-16 years, girls appeared to show a higher prevalence of addictions to the Internet and SNSs [65], but on the other hand among Turkish teacher candidates (young adults), the trend was reversed, suggesting males were significantly more likely to be addicted to using FB [66], and in a young adult Chinese group, authors reported that they did not find a relationship between gender and SNS dependence [67]. According to our results, we did not find a significant gender differences according to FB overuse and addiction behviours, but both of them were higher in female adolescents.…”
Section: Discussionmentioning
confidence: 92%
“…In a German sample with age 14-16 years, girls appeared to show a higher prevalence of addictions to the Internet and SNSs [65], but on the other hand among Turkish teacher candidates (young adults), the trend was reversed, suggesting males were significantly more likely to be addicted to using FB [66], and in a young adult Chinese group, authors reported that they did not find a relationship between gender and SNS dependence [67]. According to our results, we did not find a significant gender differences according to FB overuse and addiction behviours, but both of them were higher in female adolescents.…”
Section: Discussionmentioning
confidence: 92%
“…However, other tests are starting to be used, including the Revised Generalized and Problematic Internet Use Scale (GPIUS2) [60] and the Compulsive Internet Use Scale (CIUS) [61]. Recently, new techniques have been applied to estimate prevalence, such as latent class analysis [62]. Lastly, with regard to risk factors, common characteristics such as time spent on the Internet, online gaming, social applications, mood regulation, and desire thinking appear to increase the probability of IA, whereas other sociodemographic factors, such as gender, age, immigration, marriage, and employment status, do not.…”
Section: Main Findings Of Studies On the Prevalence Of Internet Addicmentioning
confidence: 99%
“…67 On the other hand, despite the difficulties concerning the diagnosis and heterogeneity of instruments to assess IA, most studies reporting prevalence rates for IA suffer from sampling selection biases due to systematic use of nonprobability sampling techniques (eg, convenience samples) and over-reliance on specific samples (eg, adolescents or adults). 68 Consequently, these two issues compromise the validity of most prevalence studies whilst also limiting possible comparisons of prevalence rates across different cultural contexts. In order to mitigate some of the problems related to this aspect of IA research, this section only presents findings from studies that recruited participants using probability sampling techniques and/or included nationally representative samples.…”
mentioning
confidence: 99%
“…Interestingly, prevalence rates for IA ranged from a minimum of 1% in one study to a maximum of 18.7% in another. 68,69 While all studies used cross-sectional designs to assess prevalence rates in different countries, significant heterogeneity in the assessment of IA was found alongside some arbitrariness in terms of the cutoff points adopted to ascertain prevalence rates, even when researchers had used the same instrument. It is worth mentioning that almost half of the studies included (ie, five of 12) did not assess IA with a psychometrically validated instrument.…”
mentioning
confidence: 99%